Microcystin in aquatic food webs of the Baltic and Chesapeake Bay regions. (15th May 2017) - Bukaveckas, Paul A.; Lesutienė, Jūratė; Gasiūnaitė, Zita R.; Ložys, Linas; Olenina, Irina; Pilkaitytė, Renata; Pūtys, Žilvinas; Tassone, Spencer; Wood, Joseph
Abstract: We undertook a comparative study of the James River Estuary, a sub-estuary of Chesapeake Bay, and the Curonian Lagoon, a sub-estuary of the Baltic Sea, to better understand the factors that determine the presence and persistence of algal toxins in food webs. Over a 2-year period, we measured microcystin concentrations in water, sediment and biota (fish and shellfish) at both sites. Across both food webs we found highest levels of microcystin among consumers of suspended particulate matter, including planktivorous fishes and filter-feeding shellfish, and lower levels of toxin among piscivores, scavengers and benthic omnivores. Despite similar levels of microcystin in the water column at the two sites, we observed higher toxin levels in fish and sediments of the Curonian Lagoon. We attribute this difference to the legacy of prior toxic cyanobacteria blooms in the Curonian Lagoon and hydrologic factors that result in a predominance of autochthonously-derived organic matter in the sediments at this site. Our results suggest that a consideration of species-specific differences in feeding habits, and organic matter sources supporting food webs are important to understanding the accumulation and persistence of algal toxins in food webs and should therefore be considered in assessment of risks to aquatic biota and human health.